Ejercicio para manejo del dolor crónico - Urtubia M., Viviana; Miranda M., Ana Luisa (Revista Hospital Clínico Universidad de Chile, 2015)
Chronic pain is one of the diseases which cause more impact on the functionality and quality of life of a patient. As part of the integrated management of this disease, exercise is a simple intervention, inexpensive and effective, in addition to being widely supported by the literature. The objective of this review is to show the evidence of exercise for chronic pain management through the their effects on the endogenous opioid system and activation of central pain inhibitory pathways. Likewise, this article also present some considerations in the preparticipation physical evaluation, the objectives of the exercise program and the prescription in common diseases such as chronic low back pain, osteoarthritis and fibromyalgia.